ESP COURSE DESIGN: THE NEED ANALYSIS ON ENGLISH FOR TOURISM BOOK FOR TRAVEL BUSINESS DEPARTMENT OF ELEVENTH GRADE STUDENTS AT SMKN 1 TARAKAN - Arifin, Arifin; Norain, Siti; Ridwan, Ridwan (Technium Education and Humanities, 2022)
English subject content is compared to the high school level based on the 2013 Curriculum. While English is differentiated for high school and vocational high school students for specific objectives, both high school and vocational high school students receive the same English curriculum. Finding an English textbook that matches the needs of the students in a vocational high school might be challenging. Teachers frequently lack the time necessary to create English materials for high school vocational programs. This study aims to investigate the information that should be covered in SMKN 1 Tarakan while creating an English for Tourism Book for the Travel Business Department and to ascertain the instructors’ reactions to the creation of English materials in that department. This study used a mixed-method, quantitative and qualitative analysis. The study’s findings suggest that English language material should be added. Speaking and pronunciation for language skills and components, media, pictures, and asking questions regarding pedagogical approaches are among the topics covered in the SMKN 1 Tarakan Travel Business Department’s course materials. A variety of speaking practice presentations, a variety of audio for listening, speaking, and reading practice, reading sections and texts, and some information that the learner of travel business has to be aware of make up the creation of English language products.